A review of the irradiation effect on the quality and safety of different types of meat - H. M. Qadr; N. F. Salih (Теория и практика переработки мяса, 2025)
This review explores the benefits of irradiation in improving the quality and safety of different meat types. The process involves exposing meat in a shielded room using one source of radiation that can be gamma radiation, electron beam or X-radiation for a specified period of time. Through the use of this technology, parasites, viruses, insects and bacteria can be effectively reduced, which in turn increases the lifespan and quality of meat products. According to products to be irradiated and the bacteria to be eradicated, the radiation dose could be high, low or medium. Irradiating meat at an appropriate dose does not affect its sensory qualities such as taste, texture and color. The impact of irradiation on nutritional and chemical aspects of different types of meat is complex, since free radicals can cause lipid oxidation and alter vitamins, fatty acids, and amino acids. Furthermore, irradiation can also affect physical properties of meat, such as texture and tenderness. This review also summarizes the available information on the impact of irradiation on the extension of meat shelf life.